2018
DOI: 10.2147/jir.s162486
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic tonsillitis and biofilms: a brief overview of treatment modalities

Abstract: Recurrent tonsillitis is described as when an individual suffers from several attacks of tonsillitis per year. Chronic and recurrent tonsillitis both cause repeated occurrences of inflamed tonsils which have a significant impact on a patient’s quality of life. Numerous children suffer from recurrent tonsillitis and sore throats, and these illnesses become part of their life. Antimicrobials can provide temporary relief, but in many cases, tonsillitis recurs. The cause of such recurrent infections have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 132 publications
0
16
0
2
Order By: Relevance
“…Biofilm affinity is associated to a firm attachment of the microbe and biofilm-forming microbes have a great tendency to stick permanently to the large variety of surfaces [ 3 ]. These tiny creatures’ biofilms are protected by a layer of exopolysaccharides, which can be up to 1000 times more resistant to antimicrobials, which has increased exponentially the rate of chronic infections caused by increased resistance against the host immune system and antibiotics [ 4 , 5 ]. Among such microbes is Candida albicans , a well-known resistant nosocomial bacterium primarily known for being the main cause of infectious diseases [ 6 ] such as oral thrush [ 7 ], vaginitis [ 8 ] organ transplant recipients [ 9 ] and forms of cancer in HIV/AIDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm affinity is associated to a firm attachment of the microbe and biofilm-forming microbes have a great tendency to stick permanently to the large variety of surfaces [ 3 ]. These tiny creatures’ biofilms are protected by a layer of exopolysaccharides, which can be up to 1000 times more resistant to antimicrobials, which has increased exponentially the rate of chronic infections caused by increased resistance against the host immune system and antibiotics [ 4 , 5 ]. Among such microbes is Candida albicans , a well-known resistant nosocomial bacterium primarily known for being the main cause of infectious diseases [ 6 ] such as oral thrush [ 7 ], vaginitis [ 8 ] organ transplant recipients [ 9 ] and forms of cancer in HIV/AIDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that the high degree of bacteria adhesion to epithelial surfaces serves as a basis for massive bacterial colonization, which is observed in EBV tonsillitis with the formation of membranous layers [22][23][24]. In addition to the massive adhesion of bacteria, mainly cocci, on the cells of the superficial epithelium of the tonsils of the pharynx, the phenomenon of bacterial invasion of epitheliocytes in acute EBV infection is still insufficiently studied.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Although the antibacterial resistance profile was not broad, the biofilm growth testing revealed that five out of nine S. aureus isolates and four out of five K. pneumoniae isolates were biofilm producers. Microorganisms in biofilms were distinctively more resistant to antimicrobial agents and environmental insults and were therefore more difficult to eradicate [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent tonsillitis is an infection of the palatine tonsils, which is characterized by recurrent episodes of tonsillitis, resulting in continuous discomfort in the throat, collections of debris in the palatine crypts, halitosis and cervical lymphadenopathy. Acute symptoms (episodes of tonsillitis) are induced by bacteria released from tonsillar crypts [1] Chronic symptoms are caused by bacteria sheltered within the tonsillar crypts leading to prolonged interaction with the host's immune system [1].…”
Section: Introductionmentioning
confidence: 99%